Quality Control Analysis of Handle Switch Spare Parts Using Statistical Quality Control Methods at PT XYZ - Andini, Dian; Wahyudin; Benyamine Sulaeman; Dewi Ayu Lestari (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
PT XYZ is a manufacturing company that produces motorcycle and car spare parts, during the production process, there is still a level of product defect that needs to be controlled, especially in one of the products with the highest production volume during the period of July–December 2024. This study was conducted to determine the level of damage, identify the factors causing the damage and recommend corrective actions. The method used is the Statistical Quality Control (SQC) method using statistical tools including: checksheet, histogram, pareto diagram, P-Chart, and fishbone diagram. The results of the study showed that the most product defects occurred in the short print defect type (36.61%), followed by appearance (17.42%), movement (16.08%), electric (15.77%), printing feel off (8.45%), and skip printing (5.67%). Actions taken to minimize the level of defects include conducting periodic training for operators in terms of part checking and handling procedures, compiling a visual and final inspection checklist to ensure that no steps are missed, adding a handle to the tray to prevent direct hand contact with the part/material, implementing a part inspection checklist before use including checking the dryness of the cavity, performing surface treatment such as wiping and drying the part/material before the printing process, using a cover on the part.